1988
DOI: 10.3109/00365528809093931
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Intraoesophageal pH and Gastro-oesophageal Reflux in Patients with Peptic Oesophagitis

Abstract: Simultaneous 22-h measurements of intra-oesophageal and intragastric pH were made in 22 patients with symptoms of gastro-oesophageal reflux (7 with peptic oesophagitis, 8 with peptic oesophageal stricture, and 7 with peptic oesophagitis and previous partial gastrectomy) to determine whether alkaline intra-oesophageal pH is a consequence of alkaline gastro-oesophageal reflux. In the three groups of patients intra-oesophageal pH was greater than 7 for 16.9 +/- 4.8%, 27.5 +/- 7.6%, and 21.0 +/- 7.7%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…9 While pH probes were successfully developed to accurately monitor acid reflux, measurement of bile reflux has been difficult. Indirect evidence of increased bile in the stomach with aspiration studies 10 or dual pH monitoring 11 showed an association with esophagitis and Barretts. Presence of bile in the esophagus has also been demonstrated by using prolonged esophageal aspiration studies.…”
mentioning
confidence: 97%
“…9 While pH probes were successfully developed to accurately monitor acid reflux, measurement of bile reflux has been difficult. Indirect evidence of increased bile in the stomach with aspiration studies 10 or dual pH monitoring 11 showed an association with esophagitis and Barretts. Presence of bile in the esophagus has also been demonstrated by using prolonged esophageal aspiration studies.…”
mentioning
confidence: 97%
“…Consequently, a change of 1 pH unit is the most that can be expe cted. Although accepted as a possibility (1,3), it is still an open question to what extent alkaline GER really causes a pathologic condition. It cannot be excluded that periods of alkaline pH in the esophagus, without a simultaneous alkaline pH recorded below the cardia, are of salivary origin , Simultaneous recording of gastric and esophageal pH was therefore pro-posed to detect alkaline reflux.…”
mentioning
confidence: 99%